Effect of Solidification Cooling Rate on the Microstructure Evolution and Corrosion Resistance of 2507 Super Duplex Stainless Steel - SHEN Chu, ZOU De - ning, ZHAO Jie, CHEN Yang (Cailiao Baohu, 2021)
For exploring the influence of solidification cooling rate on the microstructure evolution and corrosion resistance of 2507 super duplex stainless steel, the law of the microstructure evolution of 2507 super duplex stainless steel with different solidification cooling rates was investigated by optical microscope (OM) and scanning electron microscope (SEM). The contents of each phase in the samples with different solidification cooling rates were determined by Image - Pro image analysis software and ferrite analyzer, and the effect of solidification rate on the precipitation of σ phase and the precipitation mechanism of σ phase were obtained. Furthermore, the corrosion resistance properties of 2507 super duplex stainless steel with different solidification and cooling rates were investigated by potentiodynamic polarization and electrochemical impedance spectroscopy. Results showed that the content of σ phase in the samples structure increased with the decrease of solidification cooling rate, and the corrosion resistance of the samples weakened with the decrease of solidification cooling rate.